A comparison between modern research methods and Al-Mubarrad's brief approach (Journal of the College of Basic Education, 2023)
For more than a century, scholars have tried to return to heritage and draw from it and move its reservoirs to benefit from these reservoirs to serve humanity without discrimination. A long time has passed since attempts were made to study grammatical and linguistic sciences, and since the beginning of the twentieth century, serious attempts to study human heritage took their place in the avenue of human civilization to present treasures The different sciences folded by the hands of time and tried to bury them in the different waves of invasion in every part of the Arab world, so the need for serious and objective research arose in all subjects of science, especially the grammatical and linguistic lessons, and progress in that depends on the method and the method. The process of scientific research was set back only because of the lack of normalization of scientific curricula